Alcohol, Aggression, and Violence: From Public Health to Neuroscience - Sontate, Kajol V.; Rahim Kamaluddin, Mohammad; Naina Mohamed, Isa; Mohamed, Rashidi Mohamed Pakri; Shaikh, Mohd. Farooq; Kamal, Haziq; Kumar, Jaya (Frontiers in Psychology, 2021)
Alcohol has been associated with violent crimes and domestic violence across many nations. Various etiological factors were linked to chronic alcohol use and violence including psychiatric comorbidities of perpetrators such as personality disorders, mood disorders, and intermittent explosive disorders. Aggression is the precursor of violence and individuals prone to aggressive behaviors are more likely to commit impulsive violent crimes, especially under the influence of alcohol. Findings from brain studies indicate long-term alcohol consumption induced morphological changes in brain regions involved in self-control, decision-making, and emotional processing. In line with this, the inherent dopaminergic and serotonergic anomalies seen in aggressive individuals increase their susceptibility to commit violent crimes when alcohol present in their system. In relation to this, this article intends to investigate the influence of alcohol on aggression with sociopsychological and neuroscientific perspectives by looking into comorbidity of personality or mood disorders, state of the mind during alcohol consumption, types of beverages, environmental trigger, neurochemical changes, and gender differences that influence individual responses to alcohol intake and susceptibility to intoxicated aggression.